Teachers’ Beliefs about Causal Factors, Preventive and Contingent Actions on Bullying. A Descriptive Study - Bernardo Samuel, Kerman,; Diamante, María; Flavio, Calvo, (European Scientific Journal, ESJ, 2017)
The aim of this study was to carry out a descriptive analysis of the teachers’ beliefs about the causal factors, prevention and contingency actions about the bullying phenomenon. The study was carried out in the city of Buenos Aires, with the participation of 316 primary school teachers of the Autonomous City of Buenos Aires of both sexes (22.5% males and 77.5% females), with an age range between 22 and 69 years (M = 39.38, DE = 10.15). The sample was non-probabilistic, intentional, with proportional affixation to three quotas, according to the sex, age and socioeconomic level of the participants. After collecting the data in the field, a complete descriptive analysis of thirty items was carried out. Then a descriptive analysis of 15 final items. Finally, an analysis of the relationships between the dimensions of the scale and an analysis of the differences in the three dimensions according to the sex, age and years of experience of teachers. It is generally concluded that teachers do not believe that families of separated parents, large families or assembled families are the causal factors of harassment, teachers do not believe that competitiveness in the sports area has to do with harassment, teachers believe that parents are the most important factor in preventive actions, teachers believe that punitive actions against discrimination can be useful and finally, teachers do not believe that the change of school solves the problem of harassment